Improved Perioperative Glycemic Control by Continuous Insulin Infusion Under Supervision of an Endocrinologist Does Not Increase Costs in Patients with Diabetes - Vora, Amit C.; Saleem, Tipufaiz M.; Polomano, Rosemary C.; Eddinger, Victoria L.; Hollenbeak, Christopher S.; Girdharry, Dexter T.; Joshi, Renu; Martin, Donal; Gabbay, Robert A. (Endocrine practice, 2004)
To evaluate whether glycemic control can be improved perioperatively by implementing an insulin infusion protocol for patients with diabetes undergoing coronary artery bypass graft (CABG) surgery, without creating an additional financial burden. We also evaluated impact of such a protocol on hospital length of stay (LOS) and development of deep sternal wound infections (DSWI). We developed an insulin infusion glycemic control protocol (IGCP) under supervision and consultation of an endocrinologist. Outcomes of CABG surgery patients with diabetes receiving our IGCP (year 2000) were compared to those of a conventional group of patients with diabetes undergoing CABG prior to the use of the IGCP (year 1999). Cost analysis was performed on data from the hospital's cost accounting database, which included additional costs related to the IGCP. The IGCP group (n=107) showed significantly better glycemic control (mean blood glucose level 183.5 mg/dl +/- SD 53.2 mg/dL; P<0.0001) than the conventional group (n = 81; mean blood glucose level 241.67 mg/dL +/- 75.93 mg/dL). Overall hospital costs were not significantly affected by the intervention. The IGCP group showed a trend toward shorter LOS (IGCP 6.34 days; conventional group 6.58 days) and a reduced rate of DSWI (IGCP 4.63%; conventional group 4.94%). Glycemic control can be improved by implementation of IGCP with no significant additional health care costs. Endocrinologist involvement did not increase costs and improved glycemic management of CABG patients with diabetes.